The Performance of Pivot-Type Trailer for Fresh Fruit Bunches Transport Equipment Using Two-Wheeled Tractors in Oil Palm Fields - Idkham, Muhammad Idkham; Dhafir, Muhammad Dhafir; Safrizal, Safrizal Safrizal (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Poor farmers in Indonesia still transport palm fruit bunches manually, so they require a lot of manpower and many of them are transported for a long time, reducing quality. Oil palm farmers have two-wheeled tractors that are used for processing rice fields that can be used for towing trailers. The existing conventional trailers do not work optimally in oil palm fields, so it is necessary to design a pivot type trailer. The purpose of this study was to see the performance of the pivot type trailer for transporting oil palm fruit bunches, the pivot type trailer and the conventional one that was tested directly on the farmers' oil palm fields involving 3 operators. The results show that the pivot type trailer has an advantage over conventional trailers and is easy to operate properly, this is reflected in its very small turning radius of 260 cm unloaded and 280 cm loaded, and has a larger working capacity. Keywords: Pivot type trailers, Conveyances, Oil palm fields, Oil palm bunches,Smallholders.Â Â Â <!–[if !mso]> <![endif]–><!–[if pub]> <b:Publication type="OplPub" oty="68" oh="256"> <b:OhPrintBlock priv="30E">281</b:OhPrintBlock> <b:NuDefaultUnits priv="1004">1</b:NuDefaultUnits> <b:DptlPageDimensions type="OplPt" priv="1211"> <b:Xl priv="104">7560000</b:Xl> <b:Yl priv="204">10692000</b:Yl> </b:DptlPageDimensions> <b:DxlDefaultTab priv="1504">359410</b:DxlDefaultTab> <b:OhGallery priv="180E">259</b:OhGallery> <b:OhFancyBorders priv="190E">261</b:OhFancyBorders> <b:OhCaptions priv="1A0E">257</b:OhCaptions> <b:OhQuillDoc priv="200E">276</b:OhQuillDoc> <b:OhMailMergeData priv="210E">262</b:OhMailMergeData> <b:OhColorScheme priv="220E">279</b:OhColorScheme> <b:DwNextUniqueOid priv="2304">1</b:DwNextUniqueOid> <b:IdentGUID priv="2A07">0``````````````````````</b:IdentGUID> <b:DpgSpecial priv="2C03">5</b:DpgSpecial> <b:CTimesEdited priv="3C04">1</b:CTimesEdited> <b:NuDefaultUnitsEx priv="4104">1</b:NuDefaultUnitsEx> <b:OhImpositionEngine priv="440E">285</b:OhImpositionEngine> </b:Publication> <b:PrinterInfo type="OplPrb" oty="75" oh="281"> <b:OhColorSepBlock priv="30E">282</b:OhColorSepBlock> <b:OpmOutsidePrintMode priv="B04">1</b:OpmOutsidePrintMode> <b:FInitComplete priv="1400">False</b:FInitComplete> <b:DpiX priv="2203">0</b:DpiX> <b:DpiY priv="2303">0</b:DpiY> <b:DxlOverlap priv="2404">0</b:DxlOverlap> <b:DylOverlap priv="2504">0</b:DylOverlap> </b:PrinterInfo> <b:ColorSeperationInfo type="OplCsb" oty="79" oh="282"> <b:Plates type="OplCsp" priv="214"> <b:OplCsp type="OplCsp" priv="11"> <b:EcpPlate type="OplEcp" priv="213"> <b:Color priv="104">-1</b:Color> </b:EcpPlate> </b:OplCsp> </b:Plates> <b:DzlOverprintMost priv="304">304800</b:DzlOverprintMost> <b:CprOverprintMin priv="404">243</b:CprOverprintMin> <b:FKeepawayTrap priv="700">True</b:FKeepawayTrap> <b:CprTrapMin1 priv="904">128</b:CprTrapMin1> <b:CprTrapMin2 priv="A04">77</b:CprTrapMin2> <b:CprKeepawayMin priv="B04">255</b:CprKeepawayMin> <b:DzlTrap priv="C04">3175</b:DzlTrap> <b:DzlIndTrap priv="D04">3175</b:DzlIndTrap> <b:PctCenterline priv="E04">70</b:PctCenterline> <b:FMarksRegistration priv="F00">True</b:FMarksRegistration> <b:FMarksJob priv="1000">True</b:FMarksJob> <b:FMarksDensity priv="1100">True</b:FMarksDensity> <b:FMarksColor priv="1200">True</b:FMarksColor> <b:FLineScreenDefault priv="1300">True</b:FLineScreenDefault> </b:ColorSeperationInfo> <b:TextDocProperties type="OplDocq" oty="91" oh="276"> <b:OhPlcqsb priv="20E">278</b:OhPlcqsb> <b:EcpSplitMenu type="OplEcp" priv="A13"> <b:Color>134217728</b:Color> </b:EcpSplitMenu> </b:TextDocProperties> <b:StoryBlock type="OplPlcQsb" oty="101" oh="278"> <b:IqsbMax priv="104">1</b:IqsbMax> <b:Rgqsb type="OplQsb" priv="214"> <b:OplQsb type="OplQsb" priv="11"> <b:Qsid priv="104">1</b:Qsid> <b:TomfCopyfitBase priv="80B">-9999996.000000</b:TomfCopyfitBase> <b:TomfCopyfitBase2 priv="90B">-9999996.000000</b:TomfCopyfitBase2> </b:OplQsb> </b:Rgqsb> </b:StoryBlock> <b:ColorScheme type="OplSccm" oty="92" oh="279"> <b:Cecp priv="104">8</b:Cecp> <b:Rgecp type="OplEcp" priv="214"> <b:OplEcp priv="F">Empty</b:OplEcp> <b:OplEcp type="OplEcp" priv="111"> <b:Color>13998939</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="211"> <b:Color>3243501</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="311"> <b:Color>10395294</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="411"> <b:Color>49407</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="511"> <b:Color>9851400</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="611"> <b:Color>6697881</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="711"> <b:Color>16777215</b:Color> </b:OplEcp> </b:Rgecp> <b:IScheme priv="304">66</b:IScheme> <b:SzSchemeName priv="618">Office</b:SzSchemeName> </b:ColorScheme> <![if pub11]> <![endif]> <![endif]–><!–[if pub]> <b:Page type="OplPd" oty="67" oh="265"> <b:PtlvOrigin type="OplPt" priv="511"> <b:Xl>22858575</b:Xl> <b:Yl>22852950</b:Yl> </b:PtlvOrigin> <b:Oid priv="605">(`@`````````</b:Oid> <b:OhoplWebPageProps priv="90E">266</b:OhoplWebPageProps> <b:OhpdMaster priv="D0D">263</b:OhpdMaster> <b:PgtType priv="1004">5</b:PgtType> <b:PtlvOriginEx type="OplPt" priv="1111"> <b:Xl>110183775</b:Xl> <b:Yl>110178150</b:Yl> </b:PtlvOriginEx> </b:Page> <![endif]–><!–[if gte mso 9]> <![endif]–> Pivot type trailers, Conveyances, Oil palm fields, Oil palm bunches, Smallholders.Â Â